2004
DOI: 10.1002/yea.1147
|View full text |Cite
|
Sign up to set email alerts
|

Tandem affinity purification of the Candida albicans septin protein complex

Abstract: A novel vector was constructed to enable the integrative marking of individual genes and the affinity purification of interacting molecules within protein complexes from Candida albicans using a tandem 6×histidine and FLAG epitope tag. The system was verified by purifying the C. albicans septin complex (a self-associating complex of cytoskeletal proteins) from both yeast and hyphal cells. One-step affinity purification was insufficient for purification of the protein complex, whereas tandem affinity purificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 23 publications
1
33
0
2
Order By: Relevance
“…Quantification of the proteins levels indicated that the Cdc10/Sep7 ratios were similar during yeast and hyphal growth ( Figure 3E). These results are in good agreement with previous findings indicating that the stoichiometry of the septin complex is not affected by cell morphology (Kaneko et al, 2004). Thus, the composition of the septin ring does not substantially change during the switch from the yeast to hyphal form.…”
supporting
confidence: 93%
“…Quantification of the proteins levels indicated that the Cdc10/Sep7 ratios were similar during yeast and hyphal growth ( Figure 3E). These results are in good agreement with previous findings indicating that the stoichiometry of the septin complex is not affected by cell morphology (Kaneko et al, 2004). Thus, the composition of the septin ring does not substantially change during the switch from the yeast to hyphal form.…”
supporting
confidence: 93%
“…The data indicate evolutionary conservation of this protein complex in fungi. An unexpected finding is Hof1, which is known to localize to the bud neck and has a role in cytokinesis, but has not been found in purified septin complexes previously (Altman and Kellogg, 1997;Carroll et al, 1998;Kaneko et al, 2004). The interaction was further confirmed by co-immunoprecipitation (data not shown).…”
Section: Gin4 Phosphorylates Sep7mentioning
confidence: 87%
“…At present, we consider CaBig1p to be an adaptor protein rather than a functional enzyme because neither CaBig1p nor ScBig1p contains any amino acid motifs associated with carbohydrate-active enzymes. Using a tandem affinity purification technique, we are currently investigating whether CaBig1p and ScBig1p have binding partner proteins (15).…”
Section: Vol 74 2006mentioning
confidence: 99%